PSpice with circuit analysis - Monssen, Franz (Merrill Collier Macmillan Canada Maxwell Macmillan International Pub. Group, 1992)
This book combines coverage of circuit concepts, laws, and theories with step-by-step instruction in the corresponding PSPICE commands.